Productivity of taro (Colocasia esculenta L. Shott) under three species stands using agroforestry system in community forest site - Aris Sudomo; Aditya Hani (Jurnal Ilmu Kehutanan)
Taro (Colocasia esculenta L. Shott ) is a functional food plant. Based on Permenhut P.35/2007 with regard to Non Wood Forest Product, taro is categorized as a starch plant. According to the knowledge of local people, the agroforestry of taro has been applied on dry land of private forest. The objective of this research was to evaluate the growth and productivity of taro under three tree species of the private forest using agroforestry system. Survey and field observation were conducted in this research. Agroforestry systems were observed on sengon+taro, jabon+taro, manglid+taro, and monoculture of taro as a control. Growth and production of taro plants were measured, including height growth, number of leaves, wet and dry weight of leaves and stems. Wet and dry weight of tuber were recorded to calculate the taro production. Tree species showed significant effects on growth and production of taro plant in agroforestry system. The highest biomass of taro (366.57 g/plant) was found under jabon species, followed by sengon (266.15 g/plant), manglid (175.64 g/plant), and taro monoculture (182.98 g/plant), respectively. The light intensity under jabon tree in agroforestry system was 41.17%. The highest production of wet and dry weight of taro tuber were 2,333.0 g/plant and 884.3 g/plant, which was resulted under jabon stands, followed by under sengon stands (1,597.0 g/plant and 535.7 g/plant), under manglid stands (607.6 g/plant and 213.6 g/plant) and monoculture (739.4 g/plant and 256.3 g/plant), respectively.